Relationship Between Depression Status and Nutritional Status of Professional Study Students, Faculty of Medicine & Veterinary Medicine, Nusa Cendana University - Farrel Venedict,; Christina Olly Lada,; Regina M. Hutasoit, (International Journal Of Health Science, 2026)
Depression is a global mental disorder that affects eating patterns and physical activity, potentially leading to changes in nutritional status. Nutritional status is a key indicator of physical and mental health, and nutrient deficiencies may disrupt brain balance and mood regulation. This study aimed to examine the relationship between depression status and nutritional status among medical and veterinary professional students at Nusa Cendana University. An analytic observational study with a cross-sectional approach was conducted on 105 students. Depression status was assessed using the PHQ-9 questionnaire, while nutritional status was evaluated through Body Mass Index (BMI) and hemoglobin (Hb) levels. Statistical analysis was performed using the chi-square test with a 95% confidence level (p<0.05). The results showed that 68.5% of students experienced depression, and a significant relationship was found between depression and nutritional status (p=0.047). Students with depression tended to have imbalanced nutritional status. These findings highlight the importance of psychological support and nutritional monitoring among students.